Socioeconomic characterization of family farmers in the community of Pereira, municipality of Águas Formosas/MG - Almeida Rocha, Bernardo; Guimarães Rocha, Eduardo; Célio Souza Rocha, Luiz (Seven Editora, 2023)
Given the relevance of family farming to the Brazilian economy (Abramovay, 1998), the present study aimed to analyze the socioeconomic characteristics of family farmers in the Pereira community, in the municipality of Águas Formosas/MG. Therefore, an applied, exploratory, descriptive and qualitative research was carried out in which the technical instruments used for data collection were semi-structured interviews. Of those interviewed, 54% own areas smaller than 10 hectares, most of them have the deed to the land, practice a very diversified small-scale agriculture, 86% do not receive technical assistance, 28% live only on what they produce, have an income between R1,600.00 to R3,450.00, 57.1% have funding with resources from PRONAF and 54% of respondents have not finished elementary school. It was possible to perceive that the producers have a low level of education, they cannot support themselves only from the activity practiced in the field, they lack technical assistance, technology and access to public policies. Based on the results, public policies for family farming should: facilitate access to technical assistance; allow tenure regularization; implement business development programs; and seek production improvements with practices aimed at inserting technology in line with the preservation of the environment. DOI: https://doi.org/10.56238/tfisdwv1-160